Enhancing efficiency of perovskite solar cell via surface microstructuring: superior grain growth and light harvesting effect - Tathavadekar, Mukta C.; Agarkar, Shruti A.; Game, Onkar S.; Bansode, Umesh P.; Kulkarni, Sneha A.; Mhaisalkar, Subodh G.; Ogale, Satishchandra B. (Solar Energy, 2015)
We have introduced a novel approach to enhance the perovskite solar cell efficiency by controlling the grain growth and light harvesting properties of perovskite crystallites. Instead of using a mesoporous TiO2 layer, we have modified the surface microstructuring of the TiO2 film by dispensing nano assembled TiO2 submicron structures (nanobeads, NBs) on TiO2 compact layer. With this new approach solar cell efficiency was improved significantly through an increase in both J(sc) and V-oc. This high efficiency is attributed to crystallite size of the perovskite phase. These also act as light scattering centers giving higher current density and reduced recombination effects giving higher open circuit voltage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Grain growth; Light harvesting; Perovskite solar cells; TiO2 nanobeads